Zirconium-doped porous magadiite heterostructures upon 2D intragallery in situ hydrolysis–condensation–polymerization strategy for liquid-phase benzoylation1. Issue 83 (9th September 2015) - Ma, Yuewen; Sun, Huan; Sun, Qi; Zhang, Hui
<x xml:space="preserve">Abstract</x> Zr-doped porous magadiite heterostructures upon cosurfactant-directing 2D intragallery hydrolysis–condensation–polymerization strategy exhibit greatly enhanced Brønsted acidity and benzoylation activity.